Adaptive Control Strategy for Stationary Electric Battery Storage Systems with Reliable Peak Load Limitation at Maximum Self-Consumption of Locally Generated Energy - Florian Klausmann; Anna-Lena Klingler (Energies, 2023)
Nowadays, stationary battery storage systems are generally used to optimize the self-consumption of electricity generated locally or to limit the peak load of the local grid connection. Self-consumption optimization aims to achieve economic benefits by using more of the self-generated electricity within the local grid. Batteries used for the optimization of self-consumption tend to present low states of charge and, therefore, normally do not contribute to peak load limitation. Peak load limitation is used to minimize the grid connection power to enable more cost-efficient grid connections. However, this function can only be achieved year-round if there is sufficient surplus electricity production or if the battery can be charged from the grid. In the latter case, the batteries are often fully charged and do not significantly optimize the self-consumption. This study presents a new operating strategy that combines all the advantages of the previous operating modes with none of the disadvantages. This can be accomplished by combining the operation modes depending on the particular situation, together with a variable battery charging process. Furthermore, a simulation-based optimization procedure is introduced for the optimal configuration of the parameters. The potential of this operating strategy is demonstrated based on application examples. As a result, the operating strategy enables reliable peak load limitation all year round while simultaneously optimizing self-consumption. The operating strategy can easily be adapted to meet changing requirements such as the increasing charging power demands of electric vehicles. Thanks to a simple process based on common measured variables, the operating strategy can be integrated smoothly into practical applications.